Antitumor Activity of USP7 Inhibitor GNE-6776 in Non-Small Cell Lung Cancer Involves Regulation of Epithelial-Mesenchymal Transition, Cell Cycle, Wnt/β-Catenin, and PI3K/AKT/mTOR Pathways - Lipeng Wu; Long Lin; Meng Yu; Huajian Li; Yuanye Dang; Huosheng Liang; Guangyang Chen; Halimulati Muhetaer; Guodong Zheng; Jingjing Li; Xuejing Jia; Bo Wu; et al. (Pharmaceuticals, 2025)
Objective: Non-small cell lung cancer (NSCLC) is a major cause of cancer-related deaths worldwide. This study investigated the effects and mechanisms of the USP7 inhibitor GNE-6776 on human NSCLC A549 and H1299 cells, providing insights for anti-NSCLC drug development. Methods: USP7 expression was analyzed in lung cancer tissue using data from public databases. RNA sequencing and functional enrichment analyses were conducted to explore differentially expressed genes (DEGs) and potentially related pathways. A549 and H1299 cells were treated with GNE-6776 at different concentrations, and its effects on cell proliferation, migration, invasion, apoptosis, mitochondrial membrane potential, and cell cycle were evaluated. Changes in protein expression following GNE-6776 treatment were assessed by Western blot. A xenograft tumor model in nude mice was used to evaluate the in vivo effects of GNE-6776. Results: GNE-6776 inhibited the proliferation, migration, and invasion of A549 and H1299 cells, induced apoptosis, and caused cells to arrest in the G1 phase in a concentration-dependent manner. GNE-6776 decreased the mitochondrial membrane potential, suppressed epithelial-mesenchymal transition (EMT) markers, and downregulated the PI3K/AKT/mTOR and Wnt/β-catenin signaling pathways. GNE-6776 significantly inhibited tumor growth without affecting body weight, reduced expression of CDK6, C-myc, and N-cadherin, and increased GSK3β expression in tumor tissue. Conclusions: In summary, GNE-6776 demonstrated potent anti-tumor activity in NSCLC both in vitro and in vivo. GNE-6776 suppresses NSCLC cell proliferation, invasion, and migration while promoting apoptosis by inhibiting the EMT and modulating the PI3K/AKT/mTOR and Wnt/β-catenin pathways. These findings support its potential as a therapeutic agent for treating NSCLC.